Anomeric memory of the glycosidic bond upon fragmentation and its consequences for carbohydrate sequencing. Issue 1 (December 2017) - Schindler, Baptiste; Barnes, Loïc; Renois, Gina; Gray, Christopher; Chambert, Stéphane; Fort, Sébastien; Flitsch, Sabine; Loison, Claire; Allouche, Abdul-Rahman; Compagnon, Isabelle
Abstract Deciphering the carbohydrate alphabet is problematic due to its unique complexity among biomolecules. Strikingly, routine sequencing technologies—which are available for proteins and DNA and have revolutionised biology—do not exist for carbohydrates. This lack of structural tools is identified as a crucial bottleneck, limiting the full development of glycosciences and their considerable potential impact for the society. In this context, establishing generic carbohydrate sequencing methods is both a major scientific challenge and a strategic priority. Here we show that a hybrid analytical approach integrating molecular spectroscopy with mass spectrometry provides an adequate metric to resolve carbohydrate isomerisms, i.e the monosaccharide content, anomeric configuration, regiochemistry and stereochemistry of the glycosidic linkage. On the basis of the spectroscopic discrimination of MS fragments, we report the unexpected demonstration of the anomeric memory of the glycosidic bond upon fragmentation. This remarkable property is applied to de novo sequencing of underivatized oligosaccharides. Establishing generic carbohydrate sequencing methods is both a major scientific challenge and a strategic priority. Here the authors show a hybrid analytical approach integrating molecular spectroscopy and mass spectrometry to resolve carbohydrate isomerism, anomeric configuration, regiochemistry and stereochemistry.